2013
DOI: 10.1037/a0022949
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth and posttraumatic stress among military medical personnel.

Abstract: Military medical personnel deployed to war zones are dually burdened with stressors related to providing healthcare and combat and operational experiences. To better understand how different types and levels of stress exposure relate to positive and negative mental health outcomes among military medical personnel, the associations between combat and healthcare stress exposure and posttraumatic growth and posttraumatic stress disorder (PTSD) were examined among 253 Air Force medical personnel recently redeploye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 45 publications
2
28
2
Order By: Relevance
“…The direct effect found between exposure and peritraumatic stress symptoms is in line with previous findings of a dose‐response relationship between exposure and PTSS (e.g., McLean et al., ; Wilson, ). Current results demonstrate that this effect begins in the peritraumatic period, while exposure is ongoing.…”
Section: Discussionsupporting
confidence: 91%
“…The direct effect found between exposure and peritraumatic stress symptoms is in line with previous findings of a dose‐response relationship between exposure and PTSS (e.g., McLean et al., ; Wilson, ). Current results demonstrate that this effect begins in the peritraumatic period, while exposure is ongoing.…”
Section: Discussionsupporting
confidence: 91%
“…Five (out of a possible 10) studies reported a significant association between combat exposure and PTG, with higher levels of combat exposure being associated with higher levels of growth in four19 37 42 43 studies and a curvilinear relationship being reported in one21 study. However, the other five34 36 38 39 44 studies found a non-significant association.…”
Section: Resultsmentioning
confidence: 94%
“…Studies have sometimes limited their focus to a subsample of the military — for example, infantry,19 chaplains20 or medical personnel21 — or to a specific type of service-related trauma, for example — amputation22 or brain injury 23. Although psychological difficulties are present for a number of returning service personnel,24 there is an increased interest in PTG as a positive consequence of deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Findings concluded that moderate levels of both combat stress and caregiving stress were associated with higher levels of PTSD and PTG. This “underscores the notion that growth and emotional distress are not mutually exclusive” (McLean et al, 2011, p. 4).…”
Section: Introductionmentioning
confidence: 65%
“…Another study examined PTG in U.S. military medics, physicians, and nurses returning from deployment in the Iraq war. This study examined PTG and PTSD in 253 U.S. Air Force personnel (McLean et al, 2011). Although the study’s demographics did not identify the number of nurses included, the investigators reported that nurses were represented.…”
Section: Introductionmentioning
confidence: 99%